An Appraisal of Traditional Woven Fabric Production in Southwestern Nigeria. - K.O, Ajila (European Journal of Sustainable Development, 2016)
Abstract This study appraised factors influencing traditional woven fabric (TWF) production in South Western Nigeria. It assessed producer characteristics and, TWF techno-dynamics related variables influencing production. Purposive random and snowball sampling techniques were applied in selecting eight hundred and twenty (TWF) producers for the study. Data collected were analyzed using descriptive analysis like frequency count, percentage and mean value for interpretation and, inferential tool such as correlation analysis was used to established direction of the relationship between production and independent variables. The study identified the level of production as low. At 5% level of significant, TWF techno-dynamics related variables viz are divisibility (r = 0.769), compatibility (r = 0.754), relative advantage (r = 0.661), affordability (r = 0.513) showed relationship with production. Also, there was relationship between production and, producers characteristics such as religion (r = -0.249), tribe (r = 0.411), risk–aversion (r = 0.423), cosmopolitan(r = 0.669), perceived favorable attitude(r = 0.132) at 1% level of significant. It is then suggested that, the aforementioned variables are crucial in production and, should be given necessary attention in the application of TWF as a mechanism of economic empowerment and growth in Nigeria. Keynote: Traditional, fabric, mechanism, economic, empowerment.